Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)

Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free

Highly efficient and extremely simple protocol for the oxidation α-hydroxyphosphonates to α-ketophosphonates using Dess-Martin periodinane - Kupwade, Ravindra; Mitragotri, Satish D.; Kulkarni, Makarand A.; Desai, Uday V.; Wadagaonkar, Prakash P. (ARKIVOC, 2021)

Potassium phosphate catalyzed highly efficient synthesis of structurally diverse thioethers at ambient temperature - Mitragotri, Satish D.; Kulkarni, Makarand A.; Desai, V. Uday; Wadagaonkar, Prakash P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2022)
Commercially available potassium phosphate has been demonstrated to be a highly efficient catalyst for the synthesis of thioethers employing two different routes viz. alkylation of thiols with alkyl/aralkyl halides and by Michael addition of thiols to conjugated alkenes.
Keywords: Alkyl halides; Potassium phosphate; thia-Michael reaction; thioethers; thiols

Cyclohexylamine -an efficient organocatalyst for the synthesis of 2-amino-4H-chromene derivatives by multicomponent reactions of salicylaldehydes, active methylene compounds and nitroalkanes - Mitragotri, Satish D.; Khyadage, Poonam H.; Chorghade, Diksha S.; Kulkarni, Makarand A.; Wadagaonkar, Prakash P. (Arkivoc, 2023)
Cyclohexylamine was found to be an efficient organocatalyst for the synthesis of structurally diverse 2-amino4H-chromenes by multicomponent reaction of (substituted) salicylaldehydes, active methylene compounds and nitroalkanes at ambient temperature and under solvent-free conditions. The synthesis of a variety of 2amino-4H-chromenes was achieved using the reaction of (substituted) salicylaldehydes with two different C-H acids. The present protocol, which employed commercially available cyclohexylamine as an organocatalyst, offered the advantages of operational simplicity and avoidance of conventional purification methods and the obtained products were essentially pure.
Keywords: 2-Amino-4H-chromene; active methylene compound; cyclohexylamine; organocatalyst